2004
DOI: 10.1073/pnas.0308449101
|View full text |Cite
|
Sign up to set email alerts
|

The cholesterol membrane anchor of the Hedgehog protein confers stable membrane association to lipid-modified proteins

Abstract: The Hedgehog proteins are potent organizers of animal development. They carry a cholesterol ester at the C terminus of their signaling domain. The membrane anchoring mediated by this lipophilic modification was studied by means of an approach integrating cell biology, biochemistry, biophysics, and organic chemistry techniques. Sterol-modified and fluorescent-labeled Hedgehog-derived peptides and proteins were synthesized and investigated in biophysical and cell-biological assays. These experiments revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
83
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 26 publications
5
83
0
3
Order By: Relevance
“…This observation was supported by immunofluorescence staining of transfected cells in which the mutant IhhN proteins were found to Figure S1). The tethered IhhN proteins might have undergone an autocatalytic modification with cholesterol, which is essential for Hh membrane association [33]. Furthermore, we showed that IhhN proteins are degraded through the lysosomal pathway, as incubation with two lysosome inhibitors, chloroquine and bafilomycin, significantly reduced the degradation of IhhN proteins, but treatment with proteasome inhibitor MG132 did not ( Figure 2C).…”
Section: Enhanced Degradation Of Ihhn Proteins With Bda1 Mutations VImentioning
confidence: 63%
“…This observation was supported by immunofluorescence staining of transfected cells in which the mutant IhhN proteins were found to Figure S1). The tethered IhhN proteins might have undergone an autocatalytic modification with cholesterol, which is essential for Hh membrane association [33]. Furthermore, we showed that IhhN proteins are degraded through the lysosomal pathway, as incubation with two lysosome inhibitors, chloroquine and bafilomycin, significantly reduced the degradation of IhhN proteins, but treatment with proteasome inhibitor MG132 did not ( Figure 2C).…”
Section: Enhanced Degradation Of Ihhn Proteins With Bda1 Mutations VImentioning
confidence: 63%
“…The mature protein has a palmitic acid covalently attached to the amino terminus and a cholesterol moiety attached to the carboxyl-terminus (8). These lipid adducts confer to Hh high affinity for cell membranes (9). Nevertheless, Hh can signal to cells distant from the source (5), suggesting the involvement of specific release mechanisms of this lipid-modified protein (9).…”
mentioning
confidence: 99%
“…These lipid adducts confer to Hh high affinity for cell membranes (9). Nevertheless, Hh can signal to cells distant from the source (5), suggesting the involvement of specific release mechanisms of this lipid-modified protein (9). It has been found that dispatched (disp) gene is required exclusively in Hh-producing cells for the release of a fully functional Hh protein (10,11).…”
mentioning
confidence: 99%
“…Quasi-irreversible binding requires the presence of two long-chain anchors in the molecule, for example, palmitoyl and farnesyl, or hexadecyl and farnesyl (46). The same quasiirreversible binding is achieved with a single cholesteryl moiety (47). The use of cholesterol for membrane targeting of a peptide has just been described to increase the potency of a transitionstate ␤-secretase inhibitor (48).…”
mentioning
confidence: 99%